Understanding Vulnerability: Exploring a Person Centred Perspective - Gledhill, Clare (2022)
This dissertation aims to explore whether vulnerability is a universally experienced feeling and if so, what causes one to feel vulnerable. It also explores the concept of person-centred vulnerability and whether this could impact the way in which public services are designed and delivered.